Acute gastrointestinal injury in critically ill children: Impact on clinical outcome. (9th November 2021) - Dhochak, Nitin; Singh, Alka; Malik, Rohan; Jat, Kana R; Sankar, Jhuma; Makharia, Govind; Kabra, Sushil K; Lodha, Rakesh
Abstract : Aim: To estimate acute gastrointestinal injury (AGI) in critically ill children and association of its severity with mortality. Methods: In a prospective cohort study, critically ill children (1 month–18 years) were enrolled. Gastrointestinal symptoms over the first week of admission were classified into AGI grades 1 through 4, using a paediatric adaptation of European Society of Intensive Care Medicine AGI definitions. Performance of AGI grades in predicting 28‐day mortality was evaluated. Results: Of 151 children enrolled, 71 (47%, 95% confidence interval (CI): 38.9–55.3%) developed AGI, with AGI grades 1, 2, 3 and 4 in 22.5%, 15.9%, 6.6% and 2%, respectively. The 28‐day mortality progressively increased with AGI grade 0 (15%), 1 (35%), 2 (50%), 3 (70%), through 4 (100%), P < 0.001. Association of AGI grades with 28‐day mortality was significant even after adjustment for disease severity, age and nutritional status (odds ratio (OR) = 2.152, 95% CI: 1.455, 3.184). Among AGI grades, and paediatric logistic organ dysfunction‐2 score components, cardiovascular (OR = 1.525, 95% CI: 1.142, 2.037) and haematological (OR = 1.719, 95% CI: 1.067, 2.772) components of paediatric logistic organ dysfunction‐2 score and AGI grades (OR = 1.565, 95% CI: 1.001, 2.449) showed significant association with 28‐day mortality. Conclusions: Nearly half of the critically ill children developed AGI. AGI grades were independently associated with increased mortality, and mortality progressively increased with AGI grade.